2022
DOI: 10.1093/heapro/daac108
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the antecedents of cyberchondria: a perspective from the USA

Abstract: Summary This study establishes a theoretical framework for assessing antecedents of cyberchondria, which is a process of amplified anxiety about one’s health because of excessive online health information seeking. We examined the framework through partial least squares structural equation modeling after collecting data through a cross-sectional online survey. This research contributes to the literature by (i) evaluating the roles of health anxiety (HA) and affective responses (AR) on cyberchondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“… 7 , 21 , 24 More specifically, a meta-analysis study reported that there is a strong positive relationship between health anxiety and cyberchondria as well as a moderate positive relationship between health anxiety and OHIS. 30 Afrin and Prybutok 32 found that affective responses and health anxiety serially mediate the relationship between intolerance of uncertainty and cyberchondria among the US internet users.…”
Section: Research On Cyberchondriamentioning
confidence: 99%
“… 7 , 21 , 24 More specifically, a meta-analysis study reported that there is a strong positive relationship between health anxiety and cyberchondria as well as a moderate positive relationship between health anxiety and OHIS. 30 Afrin and Prybutok 32 found that affective responses and health anxiety serially mediate the relationship between intolerance of uncertainty and cyberchondria among the US internet users.…”
Section: Research On Cyberchondriamentioning
confidence: 99%
“…So pervasive is the problem that a cyberchondria severity scale has been proposed to help quantify the phenomenon [75]. A framework for understanding cyberchondria has been proposed, which describes a vicious circle in which compulsive seeking of online health information amplifies health anxiety, which then drives the individual to seek more online information [76].…”
Section: Cyberchondriamentioning
confidence: 99%